Clinical features and molecular characterization of Chinese patients with FKBP10 variants - Zhijia Tan; Hiu Tung Shek; Peikai Chen; Zhongxin Dong; Yapeng Zhou; Shijie Yin; Anmei Qiu; Lina Dong; Bo Gao; Michael Kai Tsun To (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Osteogenesis imperfecta (OI) is a group of rare skeletal dysplasia. Long bone deformity and scoliosis are often associated with progressively deforming types of OI. FKBP65 (encoded by FKBP10, OMIM *607063) plays a crucial role in the processing of type I procollagen. Autosomal recessive variants in FKBP10 result in type XI osteogenesis imperfecta. Methods Patients diagnosed with OI were recruited for a genetic test. RT‐PCR and Sanger sequencing were applied to confirm the splicing defect in FKBP10 mRNA with the splice‐site variant. The bone structure was characterized by Goldner's trichrome staining. Bioinformatic analyses of bulk RNA sequencing data were performed to examine the effect of the FKBP10 variant on gene expression. Results Here we reported three children from a consanguineous family harboured a homozygous splice‐site variant (c.918‐3C > G) in FKBP10 intron and developed long bone deformity and early onset of scoliosis. We also observed frequent long bone fractures and spinal deformity in another 3 OI patients with different FKBP10 variants. The homozygous splicing variant identified in the fifth intron of FKBP10 (c.918‐3C > G) led to abnormal RNA processing and loss of FKBP65 protein and consequently resulted in aberrant collagen alignment and porous bone morphology. Analysis of transcriptomic data indicated that genes involved in protein processing and osteoblast differentiation were significantly affected in the patient‐derived osteoblasts. Conclusion Our study characterized the clinical features of OI patients with FKBP10 variants and revealed the pathogenesis of the c.918‐3C > G variant. The molecular analyses helped to gain insight into the deleterious effects of FKBP10 variants on collagen processing and osteoblast differentiation.